EKSPLORASI TANAMAN YANG BERPOTENSI SEBAGAI SUMBER BAHAN BAKAR NABATI DI BUKIT JIMBARAN, BALI - RAMDHOANI RAMDHOANI; COKORDA JAVANDIRA (GANEC SWARA, 2023)
The continuously increasing oil prices make us realize that petroleum supplies are dwindling, therefore governments around the world are supporting the development of alternative fuels that are cheaper and more environmentally friendly, known as biodiesel. The research aims to measure the oil content of plants found on Jimbaran Hill. The method used is the exploration method by walking around Bukit Jimbaran. The oil is extracted from the seeds which have been dried by the soxhletation method using hexane as a solvent. The results showed that there were 14 species found on Jimbaran Hill. The highest oil content was obtained from mahogany (Swietenia mahagoni L.), namely 45.26%. This was followed by the kapok plant (Ceiba pentandra) with an oil content of 34.13%. While the lowest oil content was obtained from the orok-orok plant (Crotalaria juncea), namely 2.13%. Other non-food plants found in Bukit Jimbaran that have potential as biodiesel are the Ketapang plant (Terminalia catappa) and the butterfly plant (Bauhinia purpurea L.) with yields of 28.23% and 25.20% respectively.